From construction machines to remote construction robots: control, interfaces, and usability of the Cranebot - Duz, Alessandra; Negrello, Francesca; Rucodainii, Alexandr; Lanzoni, Daniel; Corsanici, Mario; Iapichino, Angelo; Vitali, Andrea; Regazzoni, Daniele; Birolini, Valentino; Signori, Roberto; Ceresoli, Rossano; Grioli, Giorgio; et al. (Frontiers in Robotics and AI, 2025)
Construction machines, for example cranes, excavators, or bulldozers, are widely diffused systems operating outdoors in harsh and dangerous environments, such as building sites, forests, and mines. Typically, construction machines require the on-site presence of highly skilled users to manage the complexity of their control and the high power of hydraulic actuation. Construction machines could benefit from recent developments of robot avatar technology that has demonstrated the viability of remotizing human physical activities, leveraging on intuitive interfaces and controls. Similar approaches could also improve the overall usability of construction machines, making them safer and accessible for untrained users. With this in mind, we developed a novel system for the remote control of cranes through intuitive and immersive interfaces. To validate the solution, we evaluated the experience of approximately 80 untrained users that remotely operated a crane during the 33rd Edition of Bauma, the world’s leading fair for construction machines.